# Show that if $c_1, c_2, \ldots, c_{\phi(m)}$ is a reduced residue system modulo m, $m \neq 2$ then $c_1 + \cdots+ c_{\phi(m)} \equiv 0 \pmod{m}$

Show that if $c_1, c_2,\ldots, c_{\phi(m)}$ is a reduced residue system modulo $m$, $m \neq 2$, and $m$ is a positive integer, then $c_1 +\cdots+ c_{\phi(m)} \equiv 0 \pmod{m}$

From the problem statement, I only know that $\gcd(c_i, m ) = 1$.
Is there any related theorem that I missed?

A hint would be greatly appreciated.

Thanks,
Chan

Hint $$\$$ It's a special case of Wilson's theorem for groups - see my answer here - which highlights the key role played by symmetry (here a negation reflection / involution).

Said more simply, since your set is closed under the negation reflection, its non-fixed points $$\rm -k\not\equiv k\:$$ pair up and contribute zero to the sum, leaving only the sum of its fixed points $$\rm - k\equiv k \iff 2k\equiv 0,\$$ so $$\rm\ k\equiv 0\$$ if $$\rm\: m\:$$ is odd, else $$\rm\ k \equiv 0,\ m/2$$.

• I will try to absorb this :(. Thank you. – Chan Feb 27 '11 at 2:53
• @Chan: Please feel free to ask questions if anything is not clear. I'm happy to elaborate. – Bill Dubuque Feb 27 '11 at 2:58
• Thanks for your nice offering! I really appreciated it. To be honest, sometimes I want to ask more, but I was not be able to understand it yet. So I could not even know how to ask. Sorry, I'm not a fast thinker, but I will try harder. – Chan Feb 27 '11 at 3:06
• @Chan: It's always a good idea to say something about your background when asking a question, so that replies can be aimed at the appropriate level. Here it would be helpful to know if you know any group theory, or modular arithmetic (congruences), etc. – Bill Dubuque Feb 27 '11 at 3:36
• I will next time. Thanks for your feedback. – Chan Feb 27 '11 at 5:44

HINT: If $c_i$ is a reduced residue class, then so is $m-c_i$. (Why?) and $\phi(m)$ is even $\forall m >2$

• Ambikasaran: Thanks for a great hint. – Chan Feb 27 '11 at 2:53

Clearly $g.c.d(m-1,m) = 1$. Then $\{(m-1)c_{1},(m-1)c_{2},...,(m-1)c_{\phi(m)}\}$ are all relatively prime to m; furthermore, they are mutually incongruent, since $(m-1)c_{i} \equiv (m-1)c_{j} \ \ (mod \ m)$ implies that $c_{i} \equiv c_{j} \ \ (mod \ m)$, by the cancellation law. We may thus pair each $(m-1)c_{i}$ with some $c_{j}$ such that $(m-1)c_{i} \equiv c_{j} \ \ (mod \ m)$, and we note that $c_{j}$ is uniquely defined for each $(m-1)c_{i}$. Then $$(m-1) c_{i} + (m-1)c_{w} \equiv c_{j} + (m-1)c_{w} \ \ (mod \ m) \equiv c_{j} + c_{k} \ \ (mod \ m)$$. Then $$\sum_{l=1}^{\phi(m)} (m-1) c_{l} \equiv \sum_{l=1}^{\phi(m)} c_{l} \ \ (mod \ m)$$. This implie $$2\sum_{l=1}^{\phi(m)} c_{l} \equiv m\sum_{l=1}^{\phi(m)} c_{l} \ \ (mod \ m) \equiv 0 \ \ (mod \ m)$$. If $g.c.d(2,m) = 1$, that is, m is odd, we have $$\sum_{l=1}^{\phi(m)} c_{l} \equiv 0 \ \ (mod \ m)$$.